2013
DOI: 10.1007/978-3-642-41148-9_13
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Windows File Slack Size and Stability

Abstract: Slack space can be used to hide data from the operating system and other users. While some forms of data hiding are easily detectable, others are subtle and require an experienced forensic practitioner to discover the hidden data. The amount of data that can be hidden varies with the type of slack space and environmental parameters such as filesystem block size and partition alignment. This paper evaluates the amount of file slack space available in Windows systems and the stability of slack space over time wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…For example, an 8 bit value allocated in a 16 bit boundary system, would result in 8 bits of unused memory. This is a concept similar to the use of file slack space for hiding data, and is used in tools such as bmap ( Mulazzani et al, 2013 ).…”
Section: Attack 3: a Novel Storage Based Covert Channelmentioning
confidence: 99%
“…For example, an 8 bit value allocated in a 16 bit boundary system, would result in 8 bits of unused memory. This is a concept similar to the use of file slack space for hiding data, and is used in tools such as bmap ( Mulazzani et al, 2013 ).…”
Section: Attack 3: a Novel Storage Based Covert Channelmentioning
confidence: 99%
“…For example, an 8 bit value allocated in a 16 bit boundary system, would result 8 bits of unused space. This is a concept similar to the use of file slack space for hiding data, and is used in tools such as bmap [39].…”
Section: Attack 3: a Novel Storage Based Covert Channelmentioning
confidence: 99%
“…The size of slack space can be non-trivial: A review of 18 different versions of Windows for slack space found slack (unused) space of the order of tens of megabytes (Mulazzani , 2013).…”
Section: How Data Is Stored On a Hddmentioning
confidence: 99%